[Rezension von: Domingo, Rafael, 1963-, Law and religion in a secular age] - Neoh, Joshua (A journal of church and state, 2025)
This book is largely a collection of previously published essays by the author. Part I is thematic, dealing with an assortment of issues on the relationshi